2013
DOI: 10.1007/s10552-013-0294-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of prediagnostic physical activity with survival following breast cancer diagnosis: influence of TP53 mutation status

Abstract: Purpose Physical activity both before and after breast cancer diagnosis has been associated with improved survival. However, it is not clear whether this association differs by molecular features of the tumor or by recency of the physical activity to the time of diagnosis. Methods We examined the association of prediagnostic physical activity with survival in a cohort of 1,170 women with primary, incident, and histologically confirmed breast cancer, examining tumor molecular subtypes. Cox regression models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…Physical activities, mainly of moderate-intensity are known to improve the oxidative mitochondrial capacity and promoting activity of enzymes that are responsible for oxidation of glucose and acid fatty and may lead to a dispute by glucose, thereby decreasing availability supply to the tumor cells and the influence of mutated p53 gene, which plays an apparent role of enhancing the function of these cells [9].…”
Section: The Immune System and Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Physical activities, mainly of moderate-intensity are known to improve the oxidative mitochondrial capacity and promoting activity of enzymes that are responsible for oxidation of glucose and acid fatty and may lead to a dispute by glucose, thereby decreasing availability supply to the tumor cells and the influence of mutated p53 gene, which plays an apparent role of enhancing the function of these cells [9].…”
Section: The Immune System and Cancermentioning
confidence: 99%
“…Exercise seems to have a key role in this role p53, since several studies have shown that this protein reacts to stress caused by physical exercise, the data type of stimulation can increase or decrease its nuclear expression, mitochondrial and cytoplasmic, was also reported its ability to prevent or facilitate translocation of p53 to the nucleus mitochondria [14]. In an attempt to clarify some cases, studies of the area, selected for this systematic review, seek to work with different scenarios, such as the TP53 transmutation of studying cancer patients having the mutation, working with knocked out mice, cell handling "in vitro" [9].…”
Section: P53 and Possible Interactions With Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…Some healthy behaviours, such as moderate physical activity, a healthy diet and maintenance of a healthy body weight, may lower the risk of recurrence and improve survival 2. In particular, a high level of physical activity is related to the extension of healthy lifespan3–9 and improvement of HRQOL among breast cancer survivors 3–9. Thus, international and Japanese clinical practice guidelines strongly recommend that survivors maintain high levels of physical activity 8 10.…”
Section: Introductionmentioning
confidence: 99%